Gastronomic Festival Attribute and Customer Engagement to Customer Delight Through Customer Experience and Social Interaction Value - Gitasiswhara, Gitasiswhara; Nurriyati, Ratih; Gaffar, Vanessa; Wibowo, Lili Adi; Abdullah, Taufik (Universitas Pendidikan Indonesia, 2021)
The purpose of this study is to determine the impact of gastronomic festival attributes and customer engagement on customer delight as measured by the Customer Value Experience and social interaction. Two independent variables are used in this analysis: Gastronomic Festival Attributes and Customer Engagement. The dependent variables are Customer Delight, social interaction and Customer Value Experience. The research design is quantitative, with the objective of eliciting information about the description and use of Culinary Sites in Indonesia during the covid 19 epidemics, in order to create a virtual model of Gastronomic Festival Attributes on Culinary Sites in Indonesia. As a result of the Covid 20 epidemics, the results indicated that the greatest influence is exerted by the Gastronomic Festival Attribute to Customer Value Experience. Customer Engagement results in Customer Delight, and the Gastronomic Festival Attribute results in Customer Delight as well. The research findings are intended to bolster all previously developed hypotheses, including those regarding Customer Engagement, Gastronomic Festival Attribute, Customer Value Experience, and Customer Delight.